La Abortion Evolution in the State of Mexico - Mejía-Modesto, Alfonso (Papeles de Población, 2021)
This work analyzes the measurement methods and available figures about abortion in the State of Mexico. Additionally it is proposed an alternate method for induced abortions estimation. It also includes the use of simulation models for scenery formulation and discarding figures out of range. Finally there is an analysis of theoretical approaches used in this matter.